1993
DOI: 10.1203/00006450-199304000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α, Interleukin-1β, and Interleukin-6 Plasma Levels in Neonatal Sepsis

Abstract: Tumor necrosis factor-alpha, IL-1 beta, and IL-6 are thought to be involved in the pathogenesis of sepsis with gram-negative bacteria. We studied these cytokines during neonatal sepsis with mainly gram-positive bacteria. Ten newborns with clinical sepsis and 22 healthy controls were enrolled in the study. TNF alpha plasma levels proved to be increased in the newborns with sepsis up to 560 +/- 234 pg/mL (ng/L) versus 36 +/- 4 pg/mL (ng/L) in the control group (p < 0.005), whereas IL-6 plasma levels in newborns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
3
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 0 publications
5
37
3
4
Order By: Relevance
“…The results presented by de Bont were: TNF 560 pg/mL, IL-1 18 pg/mL, IL-6 79.7 ng/mL comparing to 960 pg/mL, 968 pg/mL, 184 ng/mL in our material, respectively. 14 The results of peritoneal fluid cytokines levels demonstrated in this study are considerably higher than plasma cytokines levels in patients with NEC described in literature. Sharma described data of 27 children-mean plasma concentrations of cytokines in NEC which were accordingly: for TNF: 277 pg/ mL vs. 1,147 pg/mL, for IL-1: 499 pg/mL vs. 1,622 pg/mL and for IL-6: 316 pg/mL vs. 286,900 pg/mL in presented NEC patients.…”
Section: Discussioncontrasting
confidence: 63%
“…The results presented by de Bont were: TNF 560 pg/mL, IL-1 18 pg/mL, IL-6 79.7 ng/mL comparing to 960 pg/mL, 968 pg/mL, 184 ng/mL in our material, respectively. 14 The results of peritoneal fluid cytokines levels demonstrated in this study are considerably higher than plasma cytokines levels in patients with NEC described in literature. Sharma described data of 27 children-mean plasma concentrations of cytokines in NEC which were accordingly: for TNF: 277 pg/ mL vs. 1,147 pg/mL, for IL-1: 499 pg/mL vs. 1,622 pg/mL and for IL-6: 316 pg/mL vs. 286,900 pg/mL in presented NEC patients.…”
Section: Discussioncontrasting
confidence: 63%
“…Neutropenia was also accompanied by a decreased bacterial brain load and BBB permeability during infection. While some studies have demonstrated that the depletion of neutrophils was detrimental to the host during bacterial infection47484950, others have observed that PMN depletion prolonged host survival after infection515253. Our findings demonstrate an association between leuckocyte trafficking and BBB permeability and increased GBS penetration of the CNS, suggesting that PMN-mediated damage of the BBB has a significant role in the pathogenesis of GBS meningitis.…”
Section: Discussionmentioning
confidence: 47%
“…Early in the course of neonatal sepsis, IL-6 was produced rapidly7 9 and peaked on day 0, but its half life was short13 and could fall back to its baseline value within 24 hours. This specific property of IL-6 rendered it useful as a very early alarm hormone, but because of its short half life, clinicians could not rely on this marker alone for the diagnosis of infection, because in most circumstances it was uncertain at which stage of infection blood was taken for IL-6 determination.…”
Section: Discussionmentioning
confidence: 99%